Gottes Mühlen mahlen langsam [mahlen aber trefflich fein]... Zum Bild Gottes in der deutschen Phraseologie - Żurawlew, Tomasz (Acta Neophilologica, 2021)
The aim of this publication was to reconstruct the image of God that has been perpetuated in the German language through fixed collocations. Based on a methodological reflection, the author attempted to determine which of God’s attributes are conveyed in these expressions. Attempts were also made to identify the linguistic mechanisms that contributed to that process. The author concluded that the image of God present in German phraseology was clearly consistent with the biblical worldview. In the German language, God is depicted as someone good, just, trustworthy, but sometimes also wrathful and stern. According to the beliefs conveyed by the German language, God dwells in heaven, from which He rules over the world as God almighty. God is portrayed explicitly or implicitly, often through metaphorical and metonymic structures. God’s attributes are frequently portrayed in a language whose modality is full of reverence and supplication and is indicative of man’s dependence on Him, as well as through the use of exclusively adulatory vocabulary.